Data constitution in qualitative research with a phenomenological approach: challenge in qualitative research in digital media - Bicudo, Maria Aparecida Viggiani [UNESP]; Mocrosky, Luciane Ferreira; Orlowski, Nelem; Batista, Josiel de Oliveira; Pudelco, Marilize Nogas (Ludomedia Unipessoal Lda, 2022)
In this article, we discuss challenges that we have been facing in qualitative research with a phenomenological approach, conducted at distance, using digital technological resources. For this, we bring the description and discussion of work in progress within the Phenomenology in Mathematic Education s (FEM) and Study and Research in Teacher Formation (GEForProf) groups. These works discuss possibilities and ways in which meetings were promoted between people, as well as our style of producing qualitative research with a phenomenological approach, being at a distance, through listening. We concluded that the ways of being together at a distance required the production of training resources and the creation of links that would support meetings capable of maintaining the programmed continuity of research.
Constituição de dados na pesquisa qualitativa de abordagem fenomenológica: desafio ao pesquisar qualitativo em meios digitais
Keywords: Internet-Based Intervention; Listening; Phenomenology; Qualitative research